Analysis Of Village Revenue And Allocation Of Village Funds To Village Expenses: VILLAGE REVENUE AND ALLOCATION OF VILLAGE FUNDS TO VILLAGE EXPENSES - Wanda Nur Fauziah; Fidyah Arini Kusuma Wardhani; Datuk Maralelo S. (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study aims to determine the effect of village original income and village fund allocations on village expenditures for the 2019 to 2021 fiscal years. The independent variables in this study are Village Original Income (PAD) and Village Fund Allocation (ADD), while the dependent variable in this study is Expenditure. Village. The data analysis technique is descriptive quantitative which uses descriptive statistical analysis and the analytical method in this observation uses the correlation coefficient analysis and determination coefficient analysis. It can therefore be concluded that the initial income of the village and the allocation of village funds have a significant effect on village expenditure. effect on village expenditure